Cultura do cancelamento no Twitter “X” : racismo digitalizado na contemporaneidade - Madeira, Thiago Fernandes (2025)
This thesis investigates cancel culture on Twitter a digital microblogging platform recently rebranded as "X" from a socio-anthropological and decolonial critical perspective. The central objective is to analyze how the phenomenon of canceling Black individuals is mobilized on the network, highlighting its social, economic, and subjective impacts. The research employs multisited digital ethnography as its methodology, combined with participant observation supported by automated data collection, as well as the analysis of public episodes. Drawing on the emblematic case of Karol Conká in Big Brother Brasil 21 and other situations, the study demonstrates how digital platforms do not operate neutrally but rather reproduce and amplify structural racism. Cancel culture is understood both as a device of racialized symbolic control and as a space for resistance and denunciation. The work engages with scholars from Digital Anthropology, Decolonial Critical Theory, and Black feminist thinkers who address race, gender, class, and sexuality. The findings point to the need to understand digital networks as contested territories, shaped by racialized algorithms and practices of selective visibility, where engagement often revolves around punitive and exclusionary narratives